Manufacturing method of liquid crystal polyester and liquid crystal polyester
Patent Information
- Application Number
- JP2021565486
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2019-12-19
- Filing Date
- 2020-12-08
- Publication Date
- 2025-02-26
- Estimated Expiration
- 2040-12-08
AI Technical Summary
【0010】 本発明の液晶性ポリエステルの製造方法は、従来のナフタレンジカルボン酸を用いて製造した同じ組成の液晶性ポリエステルに比べて、機械的強度、特に引張物性に優れる液晶性ポリエステルを製造することができる。
Smart Images

Figure 0007636346000001 
Figure 0007636346000002 
Figure 0007636346000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a method for producing a liquid crystalline polyester and a liquid crystalline polyester. This application claims priority based on Japanese Patent Application No. 2019-229406, filed on December 19, 2019, the contents of which are incorporated herein by reference. [Background technology]
[0002] Liquid crystal polyesters consisting of aromatic ring skeletons have been used in recent years in the fields of electricity and electronics as materials with excellent heat resistance and tensile strength. Liquid crystal polyesters are produced, for example, by a method in which an acylated product obtained by adding acetic anhydride to an aromatic hydroxycarboxylic acid such as 4-hydroxybenzoic acid and / or an aromatic diol such as 4,4'-hydroxybiphenyl to acylate the phenolic hydroxyl group is transesterified with an aromatic dicarboxylic acid such as naphthalenedicarboxylic acid or terephthalic acid.
[0003] For example, Patent Documents 1 to 3 disclose methods for producing liquid crystalline polyesters by transesterification in the presence of naphthalenedicarboxylic acid. The liquid crystalline polyesters obtained by these methods are excellent in heat resistance and mechanical strength, and have little variation in quality, and are therefore considered to be suitable as materials for electric and electronic parts. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2005-272810 A [Patent Document 2] JP 2005-272819 A [Patent Document 3] JP 2002-037869 A Summary of the Invention [Problem to be solved by the invention]
[0005] However, in recent years, with the miniaturization of electronic components, there is a demand for further improvement in the mechanical strength of thin-walled electronic components, and there is also a demand for further improvement in the mechanical strength of thin-walled electronic components using the liquid crystalline polyesters described in these prior art documents as their materials.
[0006] An object of the present invention is to provide a method for producing a liquid crystalline polyester which can provide a liquid crystalline polyester having superior mechanical strength, particularly tensile strength, compared with a liquid crystalline polyester having the same composition produced using a conventional naphthalenedicarboxylic acid. [Means for solving the problem]
[0007] In order to solve the above problems, the present invention employs the following configuration. [1] A method for producing a liquid crystalline polyester, comprising reacting an aromatic diol (A), an aromatic hydroxycarboxylic acid (B), and a naphthalenedicarboxylic acid (C) to obtain a liquid crystalline polyester, comprising the steps of: The naphthalenedicarboxylic acid (C) is a naphthalenedicarboxylic acid powder containing 90% by mass or more of naphthalenedicarboxylic acid particles (C1) having a particle diameter of less than 150 μm as measured by the dry sieving test method of JIS K 0069 (1992). [2] The method for producing a liquid crystalline polyester according to the above [1], wherein the amount of the naphthalenedicarboxylic acid (C) used is 10 mol % or more based on the total amount (100 mol %) of the aromatic diol (A), the aromatic hydroxycarboxylic acid (B) and the naphthalenedicarboxylic acid (C) used. [3] The method for producing a liquid crystalline polyester according to [1] or [2] above, wherein the naphthalenedicarboxylic acid (C) is at least one selected from the group consisting of 2,6-naphthalenedicarboxylic acid, 2,7-naphthalenedicarboxylic acid and 1,4-naphthalenedicarboxylic acid.
[0008] [4] The method for producing a liquid crystalline polyester according to any one of the above [1] to [3], wherein the naphthalenedicarboxylic acid powder has a median particle size (D50) of 5 to 30 μm as measured by a laser diffraction / scattering method. [5] a step (i) of acylation reacting at least one of the aromatic diol (A) and the aromatic hydroxycarboxylic acid (B) with a fatty acid anhydride to obtain an acylated product; and The method for producing the liquid crystalline polyester according to any one of the above [1] to [4], further comprising a step (ii) of subjecting the acylated product to an ester exchange reaction with the naphthalenedicarboxylic acid (C) to obtain a liquid crystalline polyester. [6] The method for producing a liquid crystalline polyester according to the above [5], wherein the transesterification reaction in the step (ii) is carried out at 250 to 350°C. [7] A method comprising the steps of: (iii) preparing a naphthalenedicarboxylic acid powder containing 90 mass % or more of the naphthalenedicarboxylic acid particles (C1); The step (iii) The method includes a step (a) of classifying naphthalenedicarboxylic acid (C0) into the naphthalenedicarboxylic acid particles (C1) and the naphthalenedicarboxylic acid particles (C2) having a particle diameter of 150 μm or more by a dry sieving test method of JIS K 0069 (1992), A method for producing the liquid crystalline polyester according to any one of the above [1] to [6].
[0009] [8] A method comprising the steps of: (iii) preparing a naphthalenedicarboxylic acid powder containing 90 mass% or more of the naphthalenedicarboxylic acid particles (C1); The step (iii) (a) classifying naphthalenedicarboxylic acid (C0) into the naphthalenedicarboxylic acid particles (C1) and the naphthalenedicarboxylic acid particles (C2) having a particle diameter of 150 μm or more by a dry sieving test method of JIS K 0069 (1992); (b) processing the naphthalenedicarboxylic acid particles (C2) to prepare naphthalenedicarboxylic acid particles (C2*) having a particle diameter adjusted to less than 150 μm; and and (c) mixing the naphthalenedicarboxylic acid particles (C1) obtained in the above-mentioned operation (a) with the naphthalenedicarboxylic acid particles (C2*) obtained in the above-mentioned operation (b). A method for producing the liquid crystalline polyester according to any one of the above [1] to [7]. [9] A liquid crystalline polyester obtained by reacting an aromatic diol (A), an aromatic hydroxycarboxylic acid (B), and a naphthalenedicarboxylic acid (C), The liquid crystalline polyester is a naphthalenedicarboxylic acid powder containing 90% by mass or more of naphthalenedicarboxylic acid particles (C1) having a particle diameter of less than 150 μm as measured by the dry sieving test method of JIS K 0069 (1992). Effect of the Invention
[0010] The method for producing a liquid crystalline polyester of the present invention can produce a liquid crystalline polyester having excellent mechanical strength, particularly tensile strength, compared with a liquid crystalline polyester having the same composition produced using a conventional naphthalenedicarboxylic acid. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0011] <<Method of manufacturing liquid crystalline polyester>> First Embodiment The method for producing a liquid crystalline polyester of this embodiment is a method for producing a liquid crystalline polyester by reacting an aromatic diol (A), an aromatic hydroxycarboxylic acid (B), and a naphthalenedicarboxylic acid (C) to obtain a liquid crystalline polyester, and the naphthalenedicarboxylic acid (C) is a naphthalenedicarboxylic acid powder containing 90 mass% or more of naphthalenedicarboxylic acid particles (C1) having a particle diameter of less than 150 μm as measured by the dry sieving test method of JIS K 0069 (1992).
[0012] Naphthalenedicarboxylic acid (C) By containing 90 mass% or more of the naphthalenedicarboxylic acid particles (C1) having a particle diameter of less than 150 μm relative to 100 mass% of the total mass of the naphthalenedicarboxylic acid (C), the method for producing a liquid crystalline polyester of this embodiment can produce a liquid crystalline polyester having excellent mechanical strength, particularly tensile properties, compared to liquid crystalline polyesters of the same composition produced using conventional naphthalenedicarboxylic acids.
[0013] The naphthalenedicarboxylic acid (C) preferably contains 95 mass% or more, more preferably 98 mass% or more, and even more preferably 99 mass% or more of naphthalenedicarboxylic acid particles (C1) having a particle diameter of less than 150 μm relative to the total mass (100 mass%) of the naphthalenedicarboxylic acid (C).
[0014] The naphthalenedicarboxylic acid powder preferably has a median particle size (D50) of 5 to 30 μm, as measured by a laser diffraction / scattering method.
[0015] In this specification, the median particle size (D50) of naphthalenedicarboxylic acid powder refers to the particle size of the particle whose accumulated volume is 50% of the total volume of all particles when the particle size and volume fraction of the naphthalenedicarboxylic acid powder are measured by a laser diffraction / scattering method and the volume fractions are accumulated in ascending order of particle size.
[0016] The median particle size (D50) of the naphthalenedicarboxylic acid powder is preferably 30 μm or less, more preferably 24 μm or less, and even more preferably 14.5 μm or less. The smaller the median particle size (D50) of the naphthalenedicarboxylic acid powder, the larger the specific surface area of the naphthalenedicarboxylic acid, and the more contact points between the aromatic diol (A), the aromatic hydroxycarboxylic acid (B), and the reaction solvent and the naphthalenedicarboxylic acid powder, allowing the polycondensation reaction to proceed more quickly. The lower limit of the median particle size (D50) of the naphthalenedicarboxylic acid powder is not limited, but may be 5 μm or more, 8 μm or more, 10 μm or more, or 12 μm or more, since it is easy to pulverize with a pulverizer.
[0017] In the present embodiment, the amount of the naphthalenedicarboxylic acid (C) used is preferably 10 mol % or more, more preferably 10 to 35 mol %, further preferably 15 to 30 mol %, and particularly preferably 17.5 to 25 mol %, relative to the total amount (100 mol %) of the aromatic diol (A), the aromatic hydroxycarboxylic acid (B), and the naphthalenedicarboxylic acid (C) used.
[0018] The naphthalenedicarboxylic acid (C) is represented by the following formula (C). HOOC-Ar 3 -COOH···(C) [In the formula, Ar 3 represents a naphthylene group.
[0019] Examples of the naphthylene group include a 2,6-naphthylene group, a 1,5-naphthylene group, a 2,7-naphthylene group, a 1,4-naphthylene group, and a 1,6-naphthylene group.
[0020] Specific examples of the naphthalenedicarboxylic acid (C) in this embodiment include 2,6-naphthalenedicarboxylic acid, 1,5-naphthalenedicarboxylic acid, 2,7-naphthalenedicarboxylic acid, 1,4-naphthalenedicarboxylic acid, 1,6-naphthylene group, etc. Among these, 2,6-naphthalenedicarboxylic acid, 2,7-naphthalenedicarboxylic acid, and 1,4-naphthalenedicarboxylic acid are preferred, and 2,6-naphthalenedicarboxylic acid is most preferred.
[0021] Aromatic hydroxycarboxylic acids (B) In this specification, aromatic hydroxycarboxylic acid (B) refers to a compound having at least one aromatic ring, a hydroxy group (i.e., a phenolic hydroxyl group) directly bonded to the aromatic ring, and a carboxy group directly bonded to the aromatic ring. The aromatic ring to which the hydroxy group is bonded and the aromatic ring to which the carboxy group is bonded may be the same aromatic ring in the molecule, or may be different aromatic rings in the molecule. That is, it may be an aromatic hydroxycarboxylic acid in which a hydroxy group and a carboxy group are bonded to the same aromatic ring in the molecule, such as 4-hydroxybenzoic acid, or an aromatic hydroxycarboxylic acid in which a hydroxy group is bonded to one aromatic ring in the molecule and a carboxy group is bonded to another aromatic ring in the molecule, such as 4-hydroxy-4'-biphenylcarboxylic acid.
[0022] Examples of the aromatic hydroxycarboxylic acid (B) include aromatic hydroxycarboxylic acids represented by the following formula (B) (hereinafter, also referred to as aromatic hydroxycarboxylic acid (B)). HO-Ar 1 -COOH (B) [In the formula, Ar 1 represents an optionally substituted arylene group.
[0023] Examples of the arylene group include a phenylene group, a naphthylene group, and a biphenylylene group. The arylene group may be substituted with a halogen atom, an alkyl group having 1 to 6 carbon atoms, etc. Examples of the halogen atom include a fluorine atom, a chlorine atom, a bromine atom, and an iodine atom. Examples of the alkyl group having 1 to 6 carbon atoms include a methyl group, an ethyl group, a propyl group, an isopropyl group, a butyl group, and a t-butyl group.
[0024] Specific examples of the aromatic hydroxycarboxylic acid (B) in this embodiment include 4-hydroxybenzoic acid, 3-hydroxybenzoic acid, 2-hydroxy-6-naphthoic acid, 2-hydroxy-3-naphthoic acid, 1-hydroxy-4-naphthoic acid, 2,6-dichloro-4-hydroxybenzoic acid, 2-chloro-4-hydroxybenzoic acid, 2,6-difluoro-4-hydroxybenzoic acid, and 4-hydroxy-4'-biphenylcarboxylic acid. Among the above, 4-hydroxybenzoic acid and 2-hydroxy-6-naphthoic acid are preferred, and 2-hydroxy-6-naphthoic acid is more preferred, because they are easily available.
[0025] In the present embodiment, the aromatic hydroxycarboxylic acid (B) may be one of the above compounds, or two or more of them may be used in combination.
[0026] Aromatic diol (A) In this specification, the aromatic diol (A) refers to a compound having at least one aromatic ring and two hydroxyl groups (i.e., phenolic hydroxyl groups) directly bonded to the aromatic ring. The aromatic ring to which the hydroxyl groups are bonded may be the same aromatic ring in the molecule, or different aromatic rings in the molecule. That is, it may be an aromatic diol in which two hydroxyl groups are bonded to the same aromatic ring in the molecule, such as hydroquinone, or an aromatic diol in which a hydroxyl group is bonded to one aromatic ring in the molecule and another hydroxyl group is bonded to another aromatic ring in the molecule, such as 4,4'-dihydroxybiphenyl.
[0027] The aromatic diol (A) includes an aromatic diol represented by the following formula (A) (hereinafter, also referred to as aromatic diol (A)).
[0028] HO-Ar 2-OH (A) [In the formula, Ar 2 represents an optionally substituted arylene group or a divalent linking group represented by the following formula (IV).
[0029] [ka] [In the formula, R 1 and R 2 each independently represents a hydrogen atom, a halogen atom, an acyloxy group having 1 to 6 carbon atoms, or an alkyl group having 1 to 6 carbon atoms. X represents -O-, -S-, -SO2-, -CO-, -CH 10 - or an alkylene group.]
[0030] In the above formula (A), Ar 2 represents an optionally substituted arylene group, or a divalent linking group represented by the above formula (IV). Examples of the arylene group include a phenylene group, a naphthylene group, and a biphenylylene group. The arylene group may be substituted with a halogen atom, an alkyl group having 1 to 6 carbon atoms, an acyloxy group having 1 to 6 carbon atoms, a phenyl group, a nitro group, or the like. Examples of the halogen atom include a fluorine atom, a chlorine atom, a bromine atom, and an iodine atom. Examples of the alkyl group having 1 to 6 carbon atoms include a methyl group, an ethyl group, a propyl group, an isopropyl group, a butyl group, and a t-butyl group. Examples of the acyloxy group having 1 to 6 carbon atoms include a formyloxy group, an acetyloxy group, and a propyloxy group.
[0031] In the above formula (IV), R 1 and R 2 each independently represents a hydrogen atom, a halogen atom, an acyloxy group having 1 to 6 carbon atoms, or an alkyl group having 1 to 6 carbon atoms. Examples of the halogen atom include a fluorine atom, a chlorine atom, a bromine atom, and an iodine atom. Examples of the alkyl group having 1 to 6 carbon atoms include a methyl group, an ethyl group, a propyl group, an isopropyl group, a butyl group, and a t-butyl group. Examples of the acyloxy group having 1 to 6 carbon atoms include a formyloxy group, an acetyloxy group, and a propionyloxy group.
[0032] In the above formula (IV), X is -O-, -S-, -SO2-, -CO-, -CH 10 - or an alkylene group. The alkylene group may be a branched or straight chain alkylene group. Examples of the straight chain alkylene group include a methylene group [-CH2-], an ethylene group [-(CH2)2-], a trimethylene group [-(CH2)3-], a tetramethylene group [-(CH2)4-], and a pentamethylene group [-(CH2)5-]. Examples of branched alkylene groups include alkyl alkylene groups such as alkyl methylene groups such as -CH(CH3)-, -CH(CH2CH3)-, -C(CH3)2-, etc.; alkyl ethylene groups such as -CH(CH3)CH2-, -C(CH2CH3)2-CH2-, etc.; alkyl trimethylene groups such as -CH(CH3)CH2CH2-, -CH2CH(CH3)CH2-, etc.; and alkyl tetramethylene groups such as -CH(CH3)CH2CH2CH2-, -CH2CH(CH3)CH2CH2-, etc.
[0033] In the above formula (A), Ar 2 Examples of the group include the following groups.
[0034] [ka]
[0035] Specific examples of the aromatic diol (A) in this embodiment include 4,4'-dihydroxybiphenyl, hydroquinone, resorcinol, methylhydroquinone, 2,3,5-trimethylhydroquinone, chlorohydroquinone, acetoxyhydroquinone, nitrohydroquinone, 2,2',3,3',5,5'-hexamethyl-4,4'-biphenol, 1,4-dihydroxynaphthalene, 1,5-dihydroxynaphthalene, 1,6-dihydroxynaphthalene, 2,6-dihydroxynaphthalene, 2,7-dihydroxynaphthalene, 2,2-bis(4-hydroxyphenyl)propane, 2,2-bis(4-hydroxy-3,5-dimethylphenyl)propane, 2,2-bis(4-hydroxy-3,5-dichlorophenyl)propane, 2,2-bis(4-hydroxy-3-methylphenyl)propane, 2,2- Bis(4-hydroxy-3-chlorophenyl)propane, bis(4-hydroxyphenyl)methane, bis(4-hydroxy-3,5-dimethylphenyl)methane, bis(4-hydroxy-3,5-dichlorophenyl)methane, bis(4-hydroxy-3,5-dibromophenyl)methane, bis(4-hydroxy-3-methylphenyl)methane, bis(4-hydroxy-3-chlorophenyl)methane, 1,1-bis(4-hydroxyphenyl)cyclohexane, bis(4-hydroxyphenyl)ketone, bis(4-hydroxy-3,5-dimethylphenyl)ketone, bis(4-hydroxy-3,5-dichlorophenyl)ketone, bis(4-hydroxyphenyl)sulfide, bis(4-hydroxyphenyl)sulfone, bis(4-hydroxyphenyl)ether, and the like.
[0036] Among the above, 4,4'-dihydroxybiphenyl, hydroquinone, resorcin, 2,6-dihydroxynaphthalene, 2,7-dihydroxynaphthalene, 2,2-bis(4-hydroxyphenyl)propane, and bis-(4-hydroxyphenyl)sulfone are preferred because of their easy availability, and 4,4'-dihydroxybiphenyl and hydroquinone are more preferred.
[0037] As the aromatic diol (A) in the present embodiment, the above compounds may be used alone or in combination of two or more.
[0038] Aromatic dicarboxylic acids (D) In the method for producing a liquid crystalline polyester of the present embodiment, an aromatic dicarboxylic acid (D) other than the naphthalenedicarboxylic acid (C) may be reacted together with the naphthalenedicarboxylic acid (C).
[0039] Examples of the aromatic dicarboxylic acid (D) include aromatic dicarboxylic acids represented by the following formula (D) (hereinafter, also referred to as aromatic dicarboxylic acid (D)). HOOC-Ar 4 -COOH···(D) [In the formula, Ar 4 represents an optionally substituted arylene group or a divalent linking group represented by the following formula (IV), excluding an unsubstituted naphthylene group.
[0040] [ka] [In the formula, R 1 and R 2 each independently represents a hydrogen atom, a halogen atom, an acyloxy group having 1 to 6 carbon atoms, or an alkyl group having 1 to 6 carbon atoms. X represents -O-, -S-, -SO2-, -CO-, -CH 10 - or an alkylene group.]
[0041] Ar in the above formula (D) 4 represents an optionally substituted arylene group or a divalent linking group represented by the above formula (IV), excluding an unsubstituted naphthylene group. Examples of the arylene group include a phenylene group and a biphenylylene group. The arylene group may be substituted with a halogen atom or an alkyl group having 1 to 6 carbon atoms. Examples of the halogen atom include a fluorine atom, a chlorine atom, a bromine atom, and an iodine atom. Examples of the alkyl group having 1 to 6 carbon atoms include a methyl group, an ethyl group, a propyl group, an isopropyl group, a butyl group, and a t-butyl group.
[0042] Examples of the halogen atom, the acyloxy group having 1 to 6 carbon atoms, and the alkyl group having 1 to 6 carbon atoms are the same as those mentioned above. The divalent linking group represented by the above formula (IV) is the same as that explained in the above formula (A).
[0043] Specific examples of the aromatic dicarboxylic acid (D) include terephthalic acid, isophthalic acid, 4,4'-biphenyldicarboxylic acid, methyl terephthalic acid, methyl isophthalic acid, 4,4'-dicarboxydiphenyl ether, etc. Among these, terephthalic acid and isophthalic acid are preferred.
[0044] The method for producing a liquid crystalline polyester in the present embodiment preferably includes a step (i) of acylation reacting at least one of the aromatic diol (A) and the aromatic hydroxycarboxylic acid (B) with a fatty acid anhydride to obtain an acylated product; The method further comprises a step (ii) of subjecting the acylated product to an ester exchange reaction with the naphthalenedicarboxylic acid (C) to obtain a liquid crystalline polyester.
[0045] <Second embodiment> The method for producing a liquid crystalline polyester in the present embodiment preferably includes a step (i) of acylation reacting at least one of the aromatic diol (A) and the aromatic hydroxycarboxylic acid (B) with a fatty acid anhydride to obtain an acylated product; a step (ii) of subjecting the acylated product to an ester exchange reaction with the naphthalenedicarboxylic acid (C) to obtain a liquid crystalline polyester, The transesterification reaction in the step (ii) is carried out at 250 to 350°C.
[0046] The method for producing the liquid crystalline polyester of the present embodiment may include a step (i) of adding an aromatic diol (A), an aromatic hydroxycarboxylic acid (B) and a naphthalenedicarboxylic acid (C) together to a reaction system to obtain the acylated product, followed by a step (ii) of obtaining the liquid crystalline polyester, or a step (i) of obtaining the acylated product in the presence of an aromatic diol (A) and an aromatic hydroxycarboxylic acid (B), followed by a step (ii) of adding a naphthalenedicarboxylic acid (C) to the reaction system to obtain the liquid crystalline polyester.
[0047] [Process (i)] The step (i) is a step of subjecting at least one of the aromatic diol (A) and the aromatic hydroxycarboxylic acid (B) to an acylation reaction with a fatty acid anhydride to obtain an acylated product. Step (i) may be a step of acylation reacting both the aromatic diol (A) and the aromatic hydroxycarboxylic acid (B) with a fatty acid anhydride together to obtain an acylated product. Step (i) may be a step of acylation reaction of either the aromatic diol (A) or the aromatic hydroxycarboxylic acid (B) with a fatty acid anhydride to obtain an acylated product. In this case, a separate step of acylation reaction of the other of the aromatic diol (A) or the aromatic hydroxycarboxylic acid (B) with a fatty acid anhydride to obtain an acylated product may be provided, or a separate step of directly polymerizing the other of the aromatic diol (A) or the aromatic hydroxycarboxylic acid (B) with naphthalenedicarboxylic acid (C) may be provided.
[0048] ·Fatty acid anhydrides The fatty acid anhydride includes fatty acid anhydrides having 9 or less carbon atoms. In the present embodiment, examples of the fatty acid anhydride having 9 or less carbon atoms include acetic anhydride, propionic anhydride, butanoic anhydride, 2-methylpropionic anhydride, pentanoic anhydride, 2,2-dimethylpropionic anhydride, 2-ethylhexanoic anhydride, monochloroacetic anhydride, dichloroacetic anhydride, trichloroacetic anhydride, monobromoacetic anhydride, dibromoacetic anhydride, tribromoacetic anhydride, monofluoroacetic anhydride, difluoroacetic anhydride, trifluoroacetic anhydride, pentane-1,5-dicarboxylic anhydride, maleic anhydride, succinic anhydride, and β-bromopropionic anhydride.
[0049] In step (i) of the present embodiment, the amount of the aromatic diol (A) used is preferably 10 to 50 mol %, more preferably 20 to 40 mol %, and further preferably 20 to 30 mol %, based on the total amount (100 mol %) of the aromatic diol (A) and aromatic hydroxycarboxylic acid (B) used in step (i).
[0050] In step (i) of the present embodiment, the amount of the aromatic hydroxycarboxylic acid (B) used is preferably 50 to 90 mol %, more preferably 60 to 80 mol %, and even more preferably 70 to 80 mol %, based on the total amount (100 mol %) of the aromatic diol (A) and aromatic hydroxycarboxylic acid (B) used in step (i).
[0051] In step (i) of the present embodiment, the amount of the fatty acid anhydride having 9 or less carbon atoms used is preferably 1.01 to 1.55 equivalents, and more preferably 1.05 to 1.42 equivalents, relative to the phenolic hydroxyl group. When the amount of fatty acid anhydride used is equal to or more than the above-mentioned preferable lower limit, the equilibrium during acylation shifts to the fatty acid anhydride side, and polymerization to polyester proceeds more quickly. When the amount of the fatty acid anhydride used is equal to or less than the above-mentioned preferable upper limit, deterioration such as coloration of the resulting liquid crystalline polyester can be further suppressed.
[0052] Step (i) in this embodiment is preferably carried out at 120 to 150° C. for 10 minutes to 5 hours, more preferably at 130 to 150° C. for 20 minutes to 3 hours, and particularly preferably at 135 to 150° C. for 20 minutes to 1 hour.
[0053] [Step (ii)] The step (ii) is a step of obtaining a liquid crystalline polyester by subjecting the acylated product obtained in the above step (i) to an ester exchange reaction with the naphthalenedicarboxylic acid (C).
[0054] An aromatic dicarboxylic acid (D) other than the naphthalenedicarboxylic acid (C) may be subjected to an ester exchange reaction together with the naphthalenedicarboxylic acid (C), or an aromatic hydroxycarboxylic acid and an aromatic diol may be subjected to an ester exchange reaction together with the naphthalenedicarboxylic acid (C). The aromatic hydroxycarboxylic acid may be the same as the aromatic hydroxycarboxylic acid (B) in the above step (i).
[0055] In the step (ii) of the present embodiment, the amount of the naphthalenedicarboxylic acid (C) used is preferably 10 mol % or more, more preferably 10 to 35 mol %, further preferably 15 to 30 mol %, and particularly preferably 17.5 to 25 mol %, based on the total amount (100 mol %) of the aromatic diol (A), the aromatic hydroxycarboxylic acid (B), and the naphthalenedicarboxylic acid (C) used.
[0056] In the step (ii) of the present embodiment, the amount of the aromatic dicarboxylic acid (D) used may be 0 mol %, is preferably 0 to 15 mol %, is more preferably 0 to 10 mol %, is further preferably 0 to 5 mol %, and is particularly preferably 0 to 3 mol %, relative to the total amount (100 mol %) of the aromatic diol (A), the aromatic hydroxycarboxylic acid (B), and the naphthalenedicarboxylic acid (C).
[0057] In the step (ii) of the present embodiment, the transesterification reaction in the step (ii) is carried out at 250 to 350° C. In the step (ii) of the present embodiment, the temperature is preferably raised from 120 to 150° C. to 300 to 350° C. at a rate of 0.1 to 10° C. / min, and then the reaction is carried out at 250 to 350° C., and it is more preferable to raise the temperature from 130 to 135° C. to 280 to 330° C. at a rate of 0.3 to 5° C. / min, and then the reaction is carried out at 250 to 350° C.
[0058] When the acylated fatty acid ester and the aromatic dicarboxylic acid are subjected to an ester exchange reaction, it is preferable to distill off the by-produced fatty acid and the unreacted fatty acid anhydride from the system by evaporation in order to shift the equilibrium.
[0059] The method for producing a liquid crystalline polyester of this embodiment contains 90 mass% or more of naphthalenedicarboxylic acid particles (C1) having a particle diameter of less than 150 μm relative to 100 mass% of the total mass of the naphthalenedicarboxylic acid (C), thereby making it possible to produce a liquid crystalline polyester having superior mechanical strength, particularly tensile properties, compared to liquid crystalline polyesters of the same composition produced using conventional naphthalenedicarboxylic acids.
[0060] <Other embodiments> The method for producing a liquid crystalline polyester of the present embodiment includes a step (iii) of preparing a naphthalenedicarboxylic acid powder containing 90% by mass or more of the naphthalenedicarboxylic acid particles (C1), The step (iii) It is preferable that the method includes an operation (a) of classifying naphthalenedicarboxylic acid (C0) into the naphthalenedicarboxylic acid particles (C1) and the naphthalenedicarboxylic acid particles (C2) having a particle diameter of 150 μm or more by the dry sieving test method of JIS K 0069 (1992).
[0061] In the method for producing a liquid crystalline polyester of this embodiment, as the naphthalenedicarboxylic acid (C0), a commercially available 2,6-naphthalenedicarboxylic acid powder whose particle size has not been adjusted can be used.
[0062] The method for producing a liquid crystalline polyester of the present embodiment includes a step (iii) of preparing a naphthalenedicarboxylic acid powder containing 90% by mass or more of the naphthalenedicarboxylic acid particles (C1), The step (iii) (a) classifying naphthalenedicarboxylic acid (C0) into the naphthalenedicarboxylic acid particles (C1) and the naphthalenedicarboxylic acid particles (C2) having a particle diameter of 150 μm or more by a dry sieving test method of JIS K 0069 (1992); (b) processing the naphthalenedicarboxylic acid particles (C2) to prepare naphthalenedicarboxylic acid particles (C2*) having a particle diameter adjusted to less than 150 μm; and It is preferable to include an operation (c) of mixing the naphthalenedicarboxylic acid particles (C1) obtained in the operation (a) with the naphthalenedicarboxylic acid particles (C2*) obtained in the operation (b).
[0063] By processing naphthalenedicarboxylic acid particles (C2) having a particle diameter of 150 μm or more and adjusting the particle diameter to less than 150 μm, commercially available naphthalenedicarboxylic acid particles can be utilized as the naphthalenedicarboxylic acid particles (C2*) without waste, regardless of the particle size distribution of the particles. As a method for processing the naphthalenedicarboxylic acid particles (C2) having a particle diameter of 150 μm or more, a known pulverization method can be used.
[0064] The method for producing a liquid crystalline polyester of the present invention has the following aspects. "1" A method for producing a liquid crystalline polyester, comprising reacting an aromatic diol (A), an aromatic hydroxycarboxylic acid (B), and a naphthalenedicarboxylic acid (C) to obtain a liquid crystalline polyester, The naphthalenedicarboxylic acid (C) is a naphthalenedicarboxylic acid powder containing 90% by mass or more of naphthalenedicarboxylic acid particles (C1) having a particle diameter of less than 150 μm as measured by the dry sieving test method of JIS K 0069 (1992). "2" The method for producing a liquid crystalline polyester according to "1" above, wherein the naphthalenedicarboxylic acid (C) contains 95% by mass or more, preferably 98% by mass or more, more preferably 99% by mass or more, and even more preferably 100% by mass of naphthalenedicarboxylic acid particles (C1) having a particle diameter of less than 150 μm, based on 100% by mass of the total mass of the naphthalenedicarboxylic acid (C). "3" The method for producing a liquid crystalline polyester according to "1" or "2" above, wherein the amount of the naphthalenedicarboxylic acid (C) used is 10 mol % or more, preferably 10 to 35 mol %, more preferably 15 to 30 mol %, and further preferably 17.5 to 25 mol %, based on the total amount (100 mol %) of the aromatic diol (A), the aromatic hydroxycarboxylic acid (B), and the naphthalenedicarboxylic acid (C). "4" The method for producing a liquid crystalline polyester according to any one of the above "1" to "3", wherein the naphthalenedicarboxylic acid (C) is at least one selected from the group consisting of 2,6-naphthalenedicarboxylic acid, 2,7-naphthalenedicarboxylic acid, and 1,4-naphthalenedicarboxylic acid.
[0065] "5" The method for producing a liquid crystalline polyester according to any one of "1" to "4", wherein the naphthalenedicarboxylic acid powder has a median particle size (D50) of 5 to 30 μm, preferably 24 μm or less, and more preferably 14.5 μm or less, as measured by a laser diffraction / scattering method. "6" The method for producing a liquid crystalline polyester according to "5" above, wherein the median particle size (D50) of the naphthalenedicarboxylic acid powder is 5 μm or more, preferably 8 μm or more, more preferably 10 μm or more, and further preferably 12 μm or more. "7" a step (i) of acylation reacting at least one of the aromatic diol (A) and the aromatic hydroxycarboxylic acid (B) with a fatty acid anhydride to obtain an acylated product; and The method for producing the liquid crystalline polyester according to any one of the above items "1" to "6", further comprising a step (ii) of subjecting the acylated product to an ester exchange reaction with the naphthalenedicarboxylic acid (C) to obtain a liquid crystalline polyester. [8] The method for producing a liquid crystalline polyester according to [7] above, wherein the transesterification reaction in the step (ii) is carried out at 250 to 350°C. "9" The method includes a step (iii) of preparing a naphthalenedicarboxylic acid powder containing 90 mass% or more of the naphthalenedicarboxylic acid particles (C1), The step (iii) The method includes a step (a) of classifying naphthalenedicarboxylic acid (C0) into the naphthalenedicarboxylic acid particles (C1) and the naphthalenedicarboxylic acid particles (C2) having a particle diameter of 150 μm or more by a dry sieving test method of JIS K 0069 (1992), A method for producing a liquid crystalline polyester according to any one of the above items 1 to 8.
[0066] "10" A method comprising the step (iii) of preparing a naphthalenedicarboxylic acid powder containing 90 mass% or more of the naphthalenedicarboxylic acid particles (C1), The step (iii) (a) classifying naphthalenedicarboxylic acid (C0) into the naphthalenedicarboxylic acid particles (C1) and the naphthalenedicarboxylic acid particles (C2) having a particle diameter of 150 μm or more by a dry sieving test method of JIS K 0069 (1992); (b) processing the naphthalenedicarboxylic acid particles (C2) to prepare naphthalenedicarboxylic acid particles (C2*) having a particle diameter adjusted to less than 150 μm; and and (c) mixing the naphthalenedicarboxylic acid particles (C1) obtained in the above-mentioned operation (a) with the naphthalenedicarboxylic acid particles (C2*) obtained in the above-mentioned operation (b). A method for producing the liquid crystalline polyester according to any one of the above items "1" to "9".
[0067] <<Liquid Crystalline Polyester>> The liquid crystalline polyester in the present embodiment is a liquid crystalline polyester obtained by reacting an aromatic diol (A), an aromatic hydroxycarboxylic acid (B), and a naphthalenedicarboxylic acid (C), The naphthalenedicarboxylic acid (C) is a naphthalenedicarboxylic acid powder containing 90 mass % or more of naphthalenedicarboxylic acid particles (C1) having a particle diameter of less than 150 μm as measured by the dry sieving test method of JIS K 0069 (1992).
[0068] As described above, the liquid crystalline polyester obtained by reacting an aromatic diol (A), an aromatic hydroxycarboxylic acid (B), and a naphthalenedicarboxylic acid (C) can be made to have excellent mechanical strength, particularly tensile properties, compared to liquid crystalline polyesters of the same composition produced using conventional naphthalenedicarboxylic acids, by using a naphthalenedicarboxylic acid powder containing 90 mass% or more of naphthalenedicarboxylic acid particles (C1) having a particle diameter of less than 150 μm as the naphthalenedicarboxylic acid (C).
[0069] More specifically, the liquid crystalline polyester in this embodiment includes a liquid crystalline polyester containing a constitutional unit represented by the following formula (1) (hereinafter also referred to as constitutional unit (1)), a constitutional unit represented by the following formula (2) (hereinafter also referred to as constitutional unit (2)), and a constitutional unit represented by the following formula (3) (hereinafter also referred to as constitutional unit (3)). The liquid crystalline polyester in this embodiment may further contain a constitutional unit represented by the following formula (4) (hereinafter also referred to as constitutional unit (4)).
[0070] (1)-O-Ar 1 -CO- (2)-O-Ar 2 -O- (3)-CO-Ar 3 -CO- [In formula (1), Ar 1 represents an optionally substituted arylene group. In formula (2), Ar 2represents an optionally substituted arylene group, or a divalent linking group represented by the following formula (IV). In formula (3), Ar 3 represents a naphthylene group.
[0071] (4)-CO-Ar 4 -CO- [In the formula, Ar 4 represents an optionally substituted arylene group or a divalent linking group represented by the following formula (IV), excluding an unsubstituted naphthylene group.
[0072] [ka] [In the formula, R 1 and R 2 each independently represents a hydrogen atom, a halogen atom, an acyloxy group having 1 to 6 carbon atoms, or an alkyl group having 1 to 6 carbon atoms. X represents -O-, -S-, -SO2-, -CO-, -CH 10 - or an alkylene group.]
[0073] <Constituent unit (1)> The structural unit (1) is a structural unit represented by the above formula (1). In the above formula (1), Ar 1 represents an optionally substituted arylene group. 1 may be a phenylene group, a naphthylene group or a biphenylylene group. 1 One or more hydrogen atoms in the group represented by the following formula may be substituted with a halogen atom, an alkyl group having 1 to 10 carbon atoms, or an aryl group having 6 to 20 carbon atoms.
[0074] Ar 1 Examples of halogen atoms which can replace one or more hydrogen atoms in the above group represented by the formula: include a fluorine atom, a chlorine atom, a bromine atom and an iodine atom.
[0075] Ar 1Examples of the alkyl group having 1 to 10 carbon atoms which can be substituted for one or more hydrogen atoms in the group represented by the formula (I) include a methyl group, an ethyl group, an n-propyl group, an isopropyl group, an n-butyl group, an isobutyl group, a sec-butyl group, a tert-butyl group, an n-hexyl group, an n-heptyl group, a 2-ethylhexyl group, an n-octyl group, an n-nonyl group, and an n-decyl group.
[0076] Ar 1 Examples of the aryl group having 6 to 20 carbon atoms which can be substituted for one or more hydrogen atoms in the group represented by the formula (I) include monocyclic aromatic groups such as a phenyl group, an o-tolyl group, an m-tolyl group, and a p-tolyl group; and condensed aromatic groups such as a 1-naphthyl group and a 2-naphthyl group.
[0077] Ar 1 When one or more hydrogen atoms in the group represented by the formula (I) are substituted with these groups, the number of substitutions is preferably one or two, and more preferably one.
[0078] The structural unit (1) is a structural unit derived from a specific aromatic hydroxycarboxylic acid (B). The structural unit (1) is Ar 1 is a 1,4-phenylene group (a structural unit derived from 4-hydroxybenzoic acid), and Ar 1 is a 2,6-naphthylene group (a structural unit derived from 6-hydroxy-2-naphthoic acid).
[0079] <Constituent unit (2)> The structural unit (2) is a structural unit represented by the above formula (2). In the above formula (2), Ar 2 represents an optionally substituted arylene group or a group represented by the above formula (4). 2 may be a phenylene group, a naphthylene group, or a biphenylylene group. 2 One or more hydrogen atoms contained in may be substituted with a halogen atom, an alkyl group having 1 to 10 carbon atoms, or an aryl group having 6 to 20 carbon atoms. Ar 2The halogen atoms, alkyl groups and aryl groups which can replace one or more hydrogen atoms in the above group represented by the formula: 1 These are the same as the halogen atoms, alkyl groups having 1 to 10 carbon atoms, and aryl groups having 6 to 20 carbon atoms which can substitute for one or more hydrogen atoms in the above groups represented by the above formula (I).
[0080] Ar 2 When one or more hydrogen atoms in the group represented by the formula (I) are substituted with these groups, the number of substitutions is 2 Preferably, each of the groups represented by the formula (I) is independently 1 or 2, more preferably 1. 2 It is further preferred that is unsubstituted.
[0081] The structural unit (2) is a structural unit derived from a specific aromatic diol (A). The structural unit (2) is Ar 2 is a 1,4-phenylene group (a structural unit derived from hydroquinone), Ar 2 is a 1,3-phenylene group (a structural unit derived from 1,3-benzenediol), Ar 2 is a 2,6-naphthylene group (a structural unit derived from a structural unit derived from 2,6-dihydroxynaphthalene), Ar 2 is a 4,4'-biphenylylene group (a structural unit derived from 4,4'-dihydroxybiphenyl), or Ar 2 is preferably a diphenyl ether-4,4'-diyl group (a structural unit derived from 4,4'-dihydroxydiphenyl ether), and Ar 2 More preferably, is a 1,4-phenylene group, a 1,3-phenylene group, a 2,6-naphthylene group or a 4,4'-biphenylylene group.
[0082] <Constituent unit (3)> The structural unit (3) is a structural unit represented by the above formula (3). In the above formula (3), Ar 3represents a naphthylene group. Examples of the naphthylene group include a 2,6-naphthylene group, a 1,5-naphthylene group, a 2,7-naphthylene group, and a 1,4-naphthylene group.
[0083] The structural unit (3) is a structural unit derived from a specific naphthalenedicarboxylic acid (C). The structural unit (3) is Ar 3 is a 2,6-naphthylene group (a structural unit derived from 2,6-naphthalenedicarboxylic acid), Ar 3 is a 2,7-naphthylene group (a structural unit derived from 2,7-naphthalenedicarboxylic acid), Ar 3 is a 1,4-naphthylene group (a structural unit derived from 1,4-naphthalenedicarboxylic acid).
[0084] The divalent linking group represented by the above formula (IV) is the same as that explained in the above formula (A).
[0085] <Constituent unit (4)> The structural unit (4) is a structural unit represented by the above formula (4). In the above formula (4), Ar 4 represents an optionally substituted arylene group or a divalent linking group represented by the following formula (IV), excluding an unsubstituted naphthylene group. Ar 4 One or more hydrogen atoms contained in may be substituted with a halogen atom, an alkyl group having 1 to 10 carbon atoms, or an aryl group having 6 to 20 carbon atoms. Ar 4 Examples of the arylene group include a phenylene group and a biphenylylene group. Ar 4 The halogen atoms, alkyl groups and aryl groups which can replace one or more hydrogen atoms in the above group represented by the formula: 1 These are the same as the halogen atoms, alkyl groups having 1 to 10 carbon atoms, and aryl groups having 6 to 20 carbon atoms which can substitute for one or more hydrogen atoms in the above groups represented by the above formula (I).
[0086] Ar 4When one or more hydrogen atoms in the group represented by the formula (I) are substituted with these groups, the number of substitutions is 4 Preferably, each of the groups represented by the formula (I) is independently 1 or 2, more preferably 1. 4 It is further preferred that is unsubstituted.
[0087] Examples of the alkylidene group having 1 to 10 carbon atoms include a methylene group, an ethylidene group, an isopropylidene group, an n-butylidene group, and a 2-ethylhexylidene group, and the number of carbon atoms is preferably 1 to 10.
[0088] The structural unit (4) is a structural unit derived from a specific aromatic dicarboxylic acid. The structural unit (4) is Ar 4 is a 1,4-phenylene group (a structural unit derived from terephthalic acid), Ar 4 is a 1,3-phenylene group (a structural unit derived from isophthalic acid), Ar 4 is a 4,4'-biphenylylene group (a structural unit derived from 4,4'-dicarboxybiphenyl), or Ar 4 is preferably a diphenyl ether-4,4'-diyl group (a structural unit derived from 4,4'-dicarboxydiphenyl ether), and Ar 4 More preferably, is a 1,4-phenylene group, a 1,3-phenylene group or a 4,4'-biphenylylene group.
[0089] In the liquid crystalline polyester in this embodiment, the content of the structural unit represented by formula (1) is preferably 30 to 80 mol %, more preferably 50 to 70 mol %, and even more preferably 55 to 65 mol %, relative to the total (100 mol %) of the structural unit represented by formula (1), the structural unit represented by formula (2), and the structural unit represented by formula (3) that constitute the liquid crystalline polyester.
[0090] In the liquid crystalline polyester in this embodiment, the content of the structural unit represented by formula (1) is preferably 30 to 80 mol %, more preferably 50 to 70 mol %, and further preferably 55 to 65 mol %, relative to the total (100 mol %) of all structural units constituting the liquid crystalline polyester.
[0091] In the liquid crystalline polyester in this embodiment, the content of the structural unit represented by formula (2) is preferably 10 to 35 mol %, more preferably 15 to 30 mol %, even more preferably 17.5 to 27.5 mol %, and even more preferably 17.5 to 25 mol %, relative to the total (100 mol %) of the structural units represented by formula (1), (2), and (3) constituting the liquid crystalline polyester.
[0092] In the liquid crystalline polyester in this embodiment, the content of the structural unit represented by formula (2) is preferably 10 to 35 mol %, more preferably 15 to 30 mol %, even more preferably 17.5 to 27.5 mol %, and even more preferably 17.5 to 25 mol %, relative to the total (100 mol %) of all structural units constituting the liquid crystalline polyester.
[0093] In the liquid crystalline polyester in this embodiment, the content of the structural unit represented by formula (3) relative to the total (100 mol%) of the structural unit represented by formula (1), the structural unit represented by formula (2), and the structural unit represented by formula (3) constituting the liquid crystalline polyester is preferably 10 mol% or more, more preferably 10 to 35 mol%, even more preferably 15 to 30 mol%, particularly preferably 17.5 to 27.5 mol%, and even more preferably 17.5 to 25 mol%.
[0094] In the liquid crystalline polyester in this embodiment, the content of the structural unit represented by formula (3) is preferably 10 mol % or more, more preferably 10 to 35 mol %, even more preferably 15 to 30 mol %, particularly preferably 17.5 to 27.5 mol %, and even more preferably 17.5 to 25 mol %, relative to the total (100 mol %) of all structural units constituting the liquid crystalline polyester.
[0095] In the liquid crystalline polyester in this embodiment, the content of the structural unit represented by formula (4) is preferably 0 to 10 mol %, more preferably 0 to 5 mol %, and even more preferably 0 to 3 mol %, relative to the total (100 mol %) of the structural unit represented by formula (1), the structural unit represented by formula (2), and the structural unit represented by formula (3) constituting the liquid crystalline polyester.
[0096] In the liquid crystalline polyester in this embodiment, the content of the structural unit represented by formula (4) is preferably 0 to 10 mol %, more preferably 0 to 5 mol %, and further preferably 0 to 3 mol %, relative to the total (100 mol %) of all structural units constituting the liquid crystalline polyester.
[0097] The liquid crystalline polyester in this embodiment has a flow initiation temperature of preferably 270°C or higher, more preferably 270°C or higher and 400°C or lower, further preferably 280°C or higher and 380°C or lower, and particularly preferably 300°C or higher and 350°C or lower. When the flow starting temperature of the liquid crystalline polyester in this embodiment is within the above range, the heat resistance, strength, and rigidity are good, and the heat deterioration during molding is unlikely to occur, and the viscosity during melting is unlikely to increase, so that the flowability tends not to decrease.
[0098] The flow initiation temperature is also called the flow temperature, and is measured using a capillary rheometer at 9.8 MPa (100 kgf / cm 2When liquid crystalline polyester is melted and extruded from a nozzle with an inner diameter of 1 mm and a length of 10 mm while heating at a rate of 4°C / min under a load of 100 g / mol / L, the temperature at which the liquid crystalline polyester shows a viscosity of 4800 Pa s (48,000 poise) is reached, and this temperature is an indication of the molecular weight of liquid crystalline polyester (see "Liquid Crystal Polymer - Synthesis, Molding, Applications" edited by Koide Naoyuki, CMC Corporation, June 5, 1987, p. 95).
[0099] The liquid crystalline polyester of the present invention has the following aspects. "11" A liquid crystalline polyester obtained by reacting an aromatic diol (A), an aromatic hydroxycarboxylic acid (B), and a naphthalenedicarboxylic acid (C), The liquid crystalline polyester is a naphthalenedicarboxylic acid powder containing 90% by mass or more of naphthalenedicarboxylic acid particles (C1) having a particle diameter of less than 150 μm as measured by the dry sieving test method of JIS K 0069 (1992).
[12] A liquid crystalline polyester obtained by the method for producing a liquid crystalline polyester according to any one of [1] to
[10] above.
[0100] The liquid crystalline polyester of the present embodiment described above has excellent mechanical strength, particularly tensile strength, by containing 90 mass% or more of naphthalene dicarboxylic acid particles (C1) having a particle diameter of less than 150 μm relative to 100 mass% of the total mass of the naphthalene dicarboxylic acid (C) in the above-mentioned liquid crystalline polyester manufacturing method. EXAMPLES
[0101] The present invention will be described in more detail below with reference to specific examples, although the present invention is not limited to the following examples.
[0102] <Method for measuring particle size of naphthalenedicarboxylic acid powder> The particle size of the naphthalenedicarboxylic acid powder was measured using a mesh sieve manufactured by Tokyo Screen Co., Ltd. according to the dry sieving test method of JIS K 0069 (1992).
[0103] <Method for measuring the median particle size (D50) of naphthalenedicarboxylic acid powder> 0.1 g of the target naphthalenedicarboxylic acid powder was added to 50 mL of an aqueous solution containing Triton X-100 as a surfactant, and dispersed in an ultrasonic cleaning device for 10 minutes to prepare a dispersion liquid. Next, using a Microtrack particle size analyzer (MT-3300EXII) manufactured by Nikkiso Co., Ltd., this dispersion was irradiated with a laser beam, and the particle size distribution of the naphthalenedicarboxylic acid powder was measured by a laser diffraction method, to obtain a volume-based cumulative particle size distribution curve. In the obtained cumulative particle size distribution curve, the particle size value at the point where the cumulative volume from the fine particle side was 50% when the whole was taken as 100% was determined as the median particle size (D50).
[0104] <Naphthalenedicarboxylic acid powder> A commercially available 2,6-naphthalenedicarboxylic acid powder was subjected to synthesis of the aromatic liquid crystalline polyesters of Comparative Examples 1 to 3. The particle size of this commercially available 2,6-naphthalenedicarboxylic acid powder was measured by a dry sieving test method, and it was found that the 2,6-naphthalenedicarboxylic acid powder contained 84.9 mass% naphthalenedicarboxylic acid particles (C1) with a particle size of less than 150 μm, and the proportion of particles with a size of 150 μm or more was 15.1 mass% relative to the total mass of the 2,6-naphthalenedicarboxylic acid powder (100 mass%).The particle size of this commercially available 2,6-naphthalenedicarboxylic acid powder was measured by a laser diffraction / scattering method, and the median particle size (D50) was 15 μm.
[0105] In addition, the commercially available naphthalenedicarboxylic acid powder was passed through a sieve having an opening of 150 μm to obtain a 2,6-naphthalenedicarboxylic acid powder, which was then used in the synthesis of the aromatic liquid crystalline polyesters of Examples 1, 3 and 5. The particle size of the 2,6-naphthalenedicarboxylic acid powder obtained by passing the commercially available naphthalenedicarboxylic acid powder through a sieve with an opening of 150 μm was measured by a dry sieving test method, and it was found that the 2,6-naphthalenedicarboxylic acid powder contained 100 mass% naphthalenedicarboxylic acid particles (C1) having a particle size of less than 150 μm relative to the total mass of the 2,6-naphthalenedicarboxylic acid powder (100 mass%). The particle size of the 2,6-naphthalenedicarboxylic acid powder adjusted to a particle size of less than 150 μm by passing through a sieve with an opening of 150 μm was measured by a laser diffraction / scattering method, and the median particle size (D50) was 14 μm. In addition, the commercially available naphthalenedicarboxylic acid powder was passed through a sieve with a mesh size of 150 μm to obtain a 2,6-naphthalenedicarboxylic acid powder, and the 2,6-naphthalenedicarboxylic acid powder remaining on the sieve with a mesh size of 150 μm was mixed in a mass ratio of 95:5 to obtain a 2,6-naphthalenedicarboxylic acid powder, which was then used for the synthesis of the aromatic liquid crystalline polyesters of Examples 2, 4 and 6. The particle size of this 2,6-naphthalenedicarboxylic acid powder was measured by a laser diffraction / scattering method, and the median particle size (D50) was 14 μm.
[0106] <Measurement of flow start temperature> The flow initiation temperature of each liquid crystalline polyester was measured using a flow tester (Shimadzu Corporation, CFT-500 model). Specifically, about 2 g of each liquid crystalline polyester was filled into a capillary rheometer equipped with a die having an inner diameter of 1 mm and a length of 10 mm. Next, the filled liquid crystalline polyester was heated at a heating rate of 4°C / min under a pressure of 9.8 MPa (100 kgf / cm 2 The temperature at which the melt viscosity was 4800 Pa·s (48,000 poise) when the material was extruded from the nozzle of the rheometer under a load of 1000 MPa (1.0 MPa) was defined as the flow initiation temperature.
[0107] [Example 1] In a reactor equipped with a stirrer, torque meter, nitrogen gas inlet tube, thermometer and reflux condenser, 1129.1g (6.00 mol) of 2-hydroxy-6-naphthoic acid, 226.8g (2.06 mol) of hydroquinone, 432.4g (2.00 mol) of 2,6-naphthalenedicarboxylic acid powder adjusted to a particle size of less than 150μm by passing through a sieve with a mesh size of 150μm, 1136.5 (11.13 mol) of acetic anhydride and 0.054g of 1-methylimidazole as a catalyst were added, and the mixture was stirred at room temperature for 15 minutes, and then the temperature was raised while stirring. When the internal temperature reached 140℃, the mixture was stirred for 1 hour while maintaining the temperature at 140℃. Next, the temperature was raised from 140°C to 310°C over 5 hours while distilling off the by-product acetic acid and unreacted acetic anhydride. The mixture was kept at 310°C for 1 hour and 30 minutes to obtain an aromatic polyester. The obtained aromatic polyester was cooled to room temperature and pulverized in a pulverizer to obtain an aromatic polyester powder (particle size: about 0.1 mm to about 2 mm). The flow initiation temperature of this powder (aromatic polyester) was measured and found to be 279°C. The obtained powder was heated from 25°C to 270°C over 1 hour, then heated from 270°C to 320°C over 5 hours and 2 minutes, and then kept at 320°C for 5 hours to carry out solid-state polymerization. Thereafter, the powder after solid-state polymerization was cooled, and the flow initiation temperature of the cooled powder (aromatic liquid crystalline polyester) was measured and found to be 333°C.
[0108] [Example 2] An aromatic polyester powder was obtained in the same manner as in Example 1, except that 432.4 g (2.00 mol) of 2,6-naphthalenedicarboxylic acid powder, in which the proportion of particles with a particle diameter of less than 150 μm was 95.0 mass% and the proportion of particles with a particle diameter of 150 μm or more was 5.0 mass%, was used as the raw material 2,6-naphthalenedicarboxylic acid (particle diameter: about 0.1 mm to about 2 mm). The flow initiation temperature of this powder (aromatic polyester) was measured and found to be 279°C. The obtained powder was heated from 25°C to 270°C over 1 hour, then heated from 270°C to 320°C over 5 hours and 2 minutes, and then kept at 320°C for 5 hours to carry out solid-state polymerization. Thereafter, the powder after solid-state polymerization was cooled, and the flow initiation temperature of the cooled powder (aromatic liquid crystalline polyester) was measured and found to be 333°C.
[0109] [Comparative Example 1] An aromatic polyester powder was obtained in the same manner as in Example 1, except that 432.4 g (2.00 mol) of 2,6-naphthalenedicarboxylic acid powder, in which the proportion of particles with a particle diameter of less than 150 μm was 84.9 mass% and the proportion of particles with a particle diameter of 150 μm or more was 15.1 mass%, was used as the raw material 2,6-naphthalenedicarboxylic acid (particle diameter: about 0.1 mm to about 2 mm). The flow initiation temperature of this powder (aromatic polyester) was measured and found to be 277°C. The obtained powder was heated from 25°C to 270°C over 1 hour, then heated from 270°C to 320°C over 5 hours and 2 minutes, and then kept at 320°C for 5 hours to carry out solid-state polymerization. Thereafter, the powder after solid-state polymerization was cooled, and the flow initiation temperature of the cooled powder (aromatic liquid crystalline polyester) was measured and found to be 331°C.
[0110] [Example 3] In a reactor equipped with a stirrer, torque meter, nitrogen gas inlet tube, thermometer and reflux condenser, 1091.4g (5.80 mol) of 2-hydroxy-6-naphthoic acid, 238.2g (2.16 mol) of hydroquinone, 33.2g (0.20 mol) of terephthalic acid, 410.8g (1.90 mol) of 2,6-naphthalenedicarboxylic acid powder adjusted to a particle size of less than 150μm by passing through a sieve with a mesh size of 150μm, 1137.1 (11.14 mol) of acetic anhydride and 0.053g of 1-methylimidazole as a catalyst were added, and the mixture was stirred at room temperature for 15 minutes, and then the temperature was raised while stirring. When the internal temperature reached 140℃, the mixture was stirred for 1 hour while maintaining the temperature at 140℃. Next, the temperature was raised from 140°C to 310°C over 4 hours and 20 minutes while distilling off the by-product acetic acid and unreacted acetic anhydride. The temperature was maintained at 310°C for 1 hour and 30 minutes to obtain an aromatic polyester. The obtained aromatic polyester was cooled to room temperature and pulverized in a pulverizer to obtain an aromatic polyester powder (particle size: about 0.1 mm to about 2 mm). The flow initiation temperature of this powder (aromatic polyester) was measured and found to be 242°C. The obtained powder was heated from 25°C to 240°C over 1 hour, then heated from 240°C to 310°C over 11 hours and 40 minutes, and then kept at 310°C for 5 hours to carry out solid-state polymerization. Thereafter, the powder after solid-state polymerization was cooled, and the flow initiation temperature of the cooled powder (aromatic liquid crystalline polyester) was measured and found to be 325°C.
[0111] [Example 4] An aromatic polyester powder was obtained in the same manner as in Example 3, except that 410.8 g (1.90 mol) of 2,6-naphthalenedicarboxylic acid powder, in which the proportion of particles with a particle diameter of less than 150 μm was 95.0 mass% and the proportion of particles with a particle diameter of 150 μm or more was 5.0 mass%, was used as the raw material 2,6-naphthalenedicarboxylic acid (particle diameter: about 0.1 mm to about 2 mm). The flow initiation temperature of this powder (aromatic polyester) was measured and found to be 241°C. The obtained powder was heated from 25°C to 240°C over 1 hour, then heated from 240°C to 310°C over 11 hours and 40 minutes, and then kept at 310°C for 5 hours to carry out solid-state polymerization. Thereafter, the powder after solid-state polymerization was cooled, and the flow initiation temperature of the cooled powder (aromatic liquid crystalline polyester) was measured and found to be 324°C.
[0112] [Comparative Example 2] An aromatic polyester powder was obtained in the same manner as in Example 3, except that 410.8 g (1.90 mol) of 2,6-naphthalenedicarboxylic acid powder, in which the proportion of particles with a particle diameter of less than 150 μm was 84.9 mass% and the proportion of particles with a particle diameter of 150 μm or more was 15.1 mass%, was used as the raw material 2,6-naphthalenedicarboxylic acid (particle diameter: about 0.1 mm to about 2 mm). The flow initiation temperature of this powder (aromatic polyester) was measured and found to be 242°C. The obtained powder was heated from 25°C to 240°C over 1 hour, then heated from 240°C to 310°C over 11 hours and 40 minutes, and then kept at 310°C for 5 hours to carry out solid-state polymerization. Thereafter, the powder after solid-state polymerization was cooled, and the flow initiation temperature of the cooled powder (aromatic liquid crystalline polyester) was measured and found to be 325°C.
[0113] [Example 5] In a reactor equipped with a stirrer, torque meter, nitrogen gas inlet tube, thermometer and reflux condenser, 828.7g (6.00 mol) of 4-hydroxybenzoic acid, 226.8g (2.06 mol) of hydroquinone, 432.4g (2.00 mol) of 2,6-naphthalenedicarboxylic acid powder adjusted to a particle size of less than 150μm by passing through a sieve with a mesh size of 150μm, 1136.5 (11.13 mol) of acetic anhydride and 0.045g of 1-methylimidazole as a catalyst were added, and the mixture was stirred at room temperature for 15 minutes, and then the temperature was raised while stirring. When the internal temperature reached 140℃, the mixture was stirred for 1 hour while maintaining the temperature at 140℃. Next, the temperature was raised from 140°C to 300°C over 5 hours while distilling off the by-product acetic acid and unreacted acetic anhydride. The mixture was kept at 300°C for 1 hour and 30 minutes to obtain an aromatic polyester. The obtained aromatic polyester was cooled to room temperature and pulverized in a pulverizer to obtain an aromatic polyester powder (particle size: about 0.1 mm to about 2 mm). The flow initiation temperature of this powder (aromatic polyester) was measured and found to be 253°C. The obtained powder was heated from 25°C to 240°C over 1 hour, then heated from 240°C to 300°C over 10 hours, and then kept at 300°C for 5 hours to carry out solid-state polymerization. The powder after solid-state polymerization was then cooled, and the flow initiation temperature of the cooled powder (aromatic liquid crystalline polyester) was measured and found to be 308°C.
[0114] [Example 6] An aromatic polyester powder was obtained in the same manner as in Example 5, except that 432.4 g (2.00 mol) of 2,6-naphthalenedicarboxylic acid powder, in which the proportion of particles with a particle diameter of less than 150 μm was 95.0 mass% and the proportion of particles with a particle diameter of 150 μm or more was 5.0 mass%, was used as the raw material 2,6-naphthalenedicarboxylic acid. The flow initiation temperature of this powder (aromatic polyester) was measured and found to be 257°C. The obtained powder was heated from 25°C to 240°C over 1 hour, then heated from 240°C to 300°C over 10 hours, and then kept at 300°C for 5 hours to carry out solid-state polymerization. The powder after solid-state polymerization was then cooled, and the flow initiation temperature of the cooled powder (aromatic liquid crystalline polyester) was measured and found to be 309°C.
[0115] [Comparative Example 3] An aromatic polyester powder was obtained in the same manner as in Example 5, except that 432.4 g (2.00 mol) of 2,6-naphthalenedicarboxylic acid powder, in which the proportion of particles with a particle diameter of less than 150 μm was 84.9% by mass and the proportion of particles with a particle diameter of 150 μm or more was 15.1% by mass, was used as the raw material 2,6-naphthalenedicarboxylic acid. The flow initiation temperature of this powder (aromatic polyester) was measured and found to be 257°C. The obtained powder was heated from 25°C to 240°C over 1 hour, then heated from 240°C to 300°C over 10 hours, and then kept at 300°C for 5 hours to carry out solid-state polymerization. The powder after solid-state polymerization was then cooled, and the flow initiation temperature of the cooled powder (aromatic liquid crystalline polyester) was measured, which was 310°C.
[0116] <Evaluation of mechanical strength (tensile strength, elongation) of molded products> The aromatic liquid crystalline polyesters obtained in each of the Examples and Comparative Examples were vacuum dried at 120°C for 5 hours, and then injection molded into dumbbell test pieces (thickness 0.5 mm, length 76 mm) using an injection molding machine ("PNX-40-5A" manufactured by Nissei Plastic Industrial Co., Ltd.) under molding conditions of cylinder temperature: 350°C.
[0117] A tensile test was carried out on 20 samples of each test piece in accordance with ASTM D638 using a tensile tester (Tensilon RTG-1250, manufactured by A&D Co., Ltd.) at a chuck distance of 50 mm, a crosshead speed of 10 mm / min, and a test temperature of 25°C, to measure the tensile strength and the elongation at that time, and to calculate the average value and standard deviation of the tensile strength at break (MPa) and the tensile elongation at break (%). The results are shown in Table 1. In Table 1, the polymer composition of the aromatic liquid crystalline polyester of each Example and Comparative Example shows the content (mol%) of each constituent unit relative to the total of all constituent units (100 mol%).
[0118] [Table 1]
[0119] Explanation of abbreviations in Table 1 BON: 2-hydroxy-6-naphthoic acid POB: 4-hydroxybenzoic acid HQ: Hydroquinone NDCA: 2,6-Naphthalenedicarboxylic acid TPA: Terephthalic acid
[0120] As is clear from the results in Table 1, the aromatic liquid crystalline polyesters of Examples 1 and 2 and the aromatic liquid crystalline polyester of Comparative Example 1 have the same composition and have similar flow starting temperatures, i.e., similar molecular weights. Nevertheless, the tensile strength and elongation at that time of the aromatic liquid crystalline polyesters of Examples 1 and 2 are clearly superior to the tensile strength and elongation at that time of the aromatic liquid crystalline polyester of Comparative Example 1.
[0121] Similarly, the aromatic liquid crystalline polyesters of Examples 3 and 4 and the aromatic liquid crystalline polyester of Comparative Example 2 have the same composition, the same flow starting temperature and the same molecular weight. Nevertheless, the tensile strength and the elongation at that time of the aromatic liquid crystalline polyesters of Examples 3 and 4 are clearly superior to the tensile strength and the elongation at that time of the aromatic liquid crystalline polyester of Comparative Example 2.
[0122] Similarly, the aromatic liquid crystalline polyesters of Examples 5 and 6 and the aromatic liquid crystalline polyester of Comparative Example 3 have the same composition, the same flow starting temperature and the same molecular weight. Nevertheless, the tensile strength and the elongation at that time of the aromatic liquid crystalline polyesters of Examples 5 and 6 are clearly superior to the tensile strength and the elongation at that time of the aromatic liquid crystalline polyester of Comparative Example 3.
[0123] The aromatic liquid crystalline polyesters of Examples 1 to 6 are liquid crystalline polyesters obtained by reacting an aromatic diol (A), an aromatic hydroxycarboxylic acid (B), and a naphthalenedicarboxylic acid (C), the naphthalenedicarboxylic acid (C) being a naphthalenedicarboxylic acid powder containing 90% by mass or more of naphthalenedicarboxylic acid particles (C1) having a particle size of less than 150 μm relative to the total mass 100% of the naphthalenedicarboxylic acid (C) measured by the dry sieving test method of JIS K 0069 (1992). In contrast, the aromatic liquid crystalline polyesters of Comparative Examples 1 to 3 are liquid crystalline polyesters obtained by reacting a 2,6-naphthalenedicarboxylic acid powder having a particle size of less than 150 μm of 84.9% by mass and a particle size of 150 μm or more of 15.1% by mass.
[0124] In order to distinguish the aromatic liquid crystalline polyesters according to the examples from those according to the comparative examples, we tried to directly identify them based on their structures or properties, but we were unable to distinguish them from the various spectral data that are usually used to identify compounds. It is considered that there are circumstances in which it is impossible or impractical to directly identify the aromatic liquid crystalline polyesters according to the examples based on their structures or properties, and they can only be identified based on their manufacturing methods. [Industrial Applicability]
[0125] The method for producing a liquid crystalline polyester of the present invention is useful because it can produce a liquid crystalline polyester having excellent mechanical strength, especially tensile properties, compared with a liquid crystalline polyester having the same composition produced using conventional naphthalenedicarboxylic acid. The liquid crystalline polyester obtained by the production method of the present invention is excellent in mechanical strength such as tensile properties, heat resistance and chemical resistance, and is therefore expected to be used in various applications such as materials for thin-walled electronic components accompanying the miniaturization of electronic components.
Claims
1. A method for producing a liquid crystalline polyester, comprising reacting an aromatic diol (A), an aromatic hydroxycarboxylic acid (B), and a naphthalenedicarboxylic acid (C) to obtain a liquid crystalline polyester, comprising the steps of: The naphthalenedicarboxylic acid (C) is a naphthalenedicarboxylic acid powder containing 90 mass % or more of naphthalenedicarboxylic acid particles (C1) having a particle diameter of less than 150 μm as measured by the dry sieving test method of JIS K 0069 (1992).
2. 2. The method for producing a liquid crystalline polyester according to claim 1, wherein the amount of the naphthalenedicarboxylic acid (C) used is 10 mol % or more based on the total amount (100 mol %) of the aromatic diol (A), the aromatic hydroxycarboxylic acid (B) and the naphthalenedicarboxylic acid (C) used.
3. 3. The method for producing a liquid crystalline polyester according to claim 1, wherein the naphthalenedicarboxylic acid (C) is at least one selected from the group consisting of 2,6-naphthalenedicarboxylic acid, 2,7-naphthalenedicarboxylic acid, and 1,4-naphthalenedicarboxylic acid.
4. The method for producing a liquid crystalline polyester according to any one of claims 1 to 3, wherein the naphthalenedicarboxylic acid powder has a median particle size (D50) of 5 to 30 µm as measured by a laser diffraction / scattering method.
5. a step (i) of subjecting at least one of the aromatic diol (A) and the aromatic hydroxycarboxylic acid (B) to an acylation reaction with a fatty acid anhydride to obtain an acylated product; and The method for producing a liquid crystalline polyester according to any one of claims 1 to 4, further comprising a step (ii) of subjecting the acylated product to an ester exchange reaction with the naphthalenedicarboxylic acid (C) to obtain a liquid crystalline polyester.
6. The method for producing a liquid crystalline polyester according to claim 5, wherein the transesterification reaction in the step (ii) is carried out at 250 to 350°C.
7. (iii) preparing a naphthalenedicarboxylic acid powder containing 90% by mass or more of the naphthalenedicarboxylic acid particles (C1); The step (iii) comprises: The method includes a step (a) of classifying naphthalenedicarboxylic acid (C0) into the naphthalenedicarboxylic acid particles (C1) and the naphthalenedicarboxylic acid particles (C2) having a particle diameter of 150 μm or more by a dry sieving test method of JIS K 0069 (1992), A method for producing the liquid crystalline polyester according to any one of claims 1 to 6.
8. (iii) preparing a naphthalenedicarboxylic acid powder containing 90% by mass or more of the naphthalenedicarboxylic acid particles (C1); The step (iii) comprises: (a) classifying naphthalenedicarboxylic acid (C0) into the naphthalenedicarboxylic acid particles (C1) and the naphthalenedicarboxylic acid particles (C2) having a particle diameter of 150 μm or more by a dry sieving test method of JIS K 0069 (1992); (b) processing the naphthalenedicarboxylic acid particles (C2) to prepare naphthalenedicarboxylic acid particles (C2*) having a particle diameter adjusted to less than 150 μm; and and (c) mixing the naphthalenedicarboxylic acid particles (C1) obtained in the above-mentioned operation (a) with the naphthalenedicarboxylic acid particles (C2*) obtained in the above-mentioned operation (b). A method for producing the liquid crystalline polyester according to any one of claims 1 to 7.
9. A liquid crystalline polyester obtained by reacting an aromatic diol (A), an aromatic hydroxycarboxylic acid (B), and a naphthalenedicarboxylic acid (C), The liquid crystalline polyester, wherein the naphthalenedicarboxylic acid (C) is a naphthalenedicarboxylic acid powder containing 90% by mass or more of naphthalenedicarboxylic acid particles (C1) having a particle diameter of less than 150 μm as measured by the dry sieving test method of JIS K 0069 (1992).
Citation Information
Patent Citations
JP1974037599A
Aromatic dicarboxylic acid composition and crystalline polyester resin using the same
JP2002037869A
Thermotropic liquid crystal polymer
JP2002371127A
Aromatic polyester
JP2004002697A
Liquid crystal polyester resin composition
JP2005213418A